ANALISIS KETERKAITAN KUALITAS PELAYANAN TERHADAP CONSUMER SATISFACTION MINIMARKET 212 DI KOTA MEDAN - DAYU, Wulan (IAIN Langsa, 2019)
This study aims to test the service qualities that affects of the consumers satisfaction who come to visit or shop for daily necessities at Minimarket 212 (212 Mart) in kota Medan and surrounding areas. The population in this study were all consumers who came and shopped in Minimarket 212 (212 Mart) in kota Medan and surrounding areas. The sampling technique uses incidental sampling combined with the moe formula (marginal of maximal error), so that the number of research samples is 100 people. The analysis technique used in this study is multiple linear regression analysis with SPSS version 21.0 for Windows application which aims to obtain a comprehensive picture of the relationship of the research variables. The results of this study indicate variable servant quality in the form of reliability, assurance and empathy has a significant influence on customer satisfaction who come and shop at Minimarket 212 (212 Mart) in kota Medan and surrounding areas. While service quality variables in the form of tengible and responsiveness hasn’t a significant effect on customer satisfaction who come and shop at Minimarket 212 (212 Mart) in kota Medan and surrounding areas.